Enhanced detection of explosives by turn-on resonance Raman upon host–guest complexation in solution and the solid state. Issue 79 (20th September 2017) - Witlicki, Edward H.; Bähring, Steffen; Johnsen, Carsten; Solano, Marta V.; Nielsen, Kent A.; Silverstein, Daniel W.; Marlatt, Craig W.; Jensen, Lasse; Jeppesen, Jan O.; Flood, Amar H.
Abstract : Being colour coordinated allows turn on detection of nitroaromatics by combining molecular recognition with resonant enhancement of the Raman spectra. Abstract : The recognition of nitroaromatic explosives by a tetrakis-tetrathiafulvalene-calix[4]pyrrole receptor (TTF-C[4]P) yields a "turn on" and fingerprinting response in the resonance Raman scattering observed in solution and the solid state. Intensity changes in nitro vibrations with analyte complexation occur via a mechanism of resonance between the 785 nm laser line and the strongly absorbing charge-transfer chromophore arising from the complex between electron-donating TTF-C[4]P and electron-accepting nitroaromatic explosives. The addition of chloride forms the Cl − ·TTF-C[4]P complex resetting the system for reuse.